Ocular Complications After Radiation Therapy: An Observational Study - Nuzzi R (Dove Medical Press, 2020)
Raffaele Nuzzi,1 Marta Trossarello,1 Sara Bartoncini,2 Paola Marolo,1 Pierfrancesco Franco,2 Cristina Mantovani,2 Umberto Ricardi2 1Department of Surgical Sciences, Ophthalmology/Eye Clinic, University of Turin, Turin, Italy; 2Department of Oncology, University of Turin, Turin, ItalyCorrespondence: Raffaele NuzziDipartimento di Scienze Chirurgiche, Ophthalmology/Eye Clinic, University of Turin, Oculistica U, Via Cherasco 23, Turin 10126, ItalyTel +39 368 203 493Email raffaele.nuzzi@unito.itAim of the Study: The study aims to quantify the incidence of ocular complications in patients irradiated on the head and neck area in our medical center, stratified by type of neoplasm and radiation dose received.Materials and Methods: From an existing database of patients radio-treated in our center, we selected 25 patients irradiated in the 2011– 2018 period. The patients had been treated for orbital lymphoma, nasopharyngeal carcinoma and cranial base meningioma. The selected patients received an ophthalmologic evaluation which included a complete ophthalmological and orthoptic assessment.Results: Our results showed a significantly higher incidence of DES (dry eye syndrome) and corneal complications for eyes receiving a Dmax higher than 40 Gy, as well as for cataract incidence in eyes that had received a Dmax to the lens higher than 5 Gy. We found an overall thinning of the RNFL (retinal nerve fiber layer) in eyes that had received a Dmax higher than 50 Gy, as well as a greater MD (mean deviation) from normal visual field values.Conclusion: In conclusion, we can say that the study confirms the presence of a correlation between the received radiation dose and the onset of eye complications, despite the small sample.Keywords: eye, radiotherapy, orbital lymphoma, nasopharyngeal carcinoma, meningioma, secondary/iatrogenic pathology